IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI BUDAYA RELIGIUS DI SMP PGRI 01 KARANGPLOSO MALANG - Abidatul Izzah; AzhaR Haq; Nur Hasan (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The implementation of learning Islamic religious education through religious culture is one of the school's efforts in shaping religious students through religious activities in schools. This happens because as a fort to avoid external influences that are not good and the condition of students who come from different religious backgrounds. This research was conducted in SMP PGRI 01 Karangploso Malang. This study uses a type of qualitative research using a descriptive qualitative research approach. In this study, it has a characteristic that lies in its main purpose, which is to describe everything related to implementing the learning of Islamic religious education through religious culture in schools. The results of this study are that there are several school activities that reflect religious activities, and there are obstacles that occur during the implementation of activities and there are efforts made by Principals and teachers in the implementation of learning Islamic religious education through religious culture.The implementation of learning Islamic religious education through religious culture is one of the school's efforts in shaping religious students through religious activities in schools. This happens because as a fort to avoid external influences that are not good and the condition of students who come from different religious backgrounds. This research was conducted in SMP PGRI 01 Karangploso Malang. This study uses a type of qualitative research using a descriptive qualitative research approach. In this study, it has a characteristic that lies in its main purpose, which is to describe everything related to implementing the learning of Islamic religious education through religious culture in schools. The results of this study are that there are several school activities that reflect religious activities, and there are obstacles that occur during the implementation of activities and there are efforts made by Principals and teachers in the implementation of learning Islamic religious education through religious culture.